Killer whales attack on South American sea lion associated with a fishing vessel: predator and prey tactics - Grandi,M. Florencia (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2012)
Interactions between killer whales and sea lions are widely known. This work describes the predator-prey behaviour of killer whales and South American sea lion associated with a trawling fishery. In Argentina the predatory behaviours of killer whales and anti-predatory behaviours of South American sea lions have been described from costal based observations, but predator-prey behaviour of these species is poorly known at open waters. Here we describe a killer whale group attack on an individual sea lion, using a video recorded from a trawling vessel and an interview of the ship captain. This predator-prey behaviour represents an example of the complexity of interactions between marine mammals and fisheries along the Patagonian coast.